1988
DOI: 10.1002/aja.1001810209
|View full text |Cite
|
Sign up to set email alerts
|

Nascent muscle fiber appearance in overloaded chicken slow‐tonic muscle

Abstract: The application of a weight overload to the humerus of chickens induces a hypertrophy of anterior latissimus dorsi (ALD) muscle fibers. This growth is accompanied by a rapid and almost complete replacement of one slow-tonic myosin isoform, SM-1, by another slow-tonic isoform, SM-2. In addition, a population of small fibers appears mainly in extrafascicular spaces and, concurrently, three additional myosin bands are detected by gel electrophoresis. Five antibodies against myosin heavy chain (MHC) isoforms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 52 publications
6
52
1
Order By: Relevance
“…Stretch-induced hypertrophy of avian wing muscle has also been implicated in the activation of satellite cells (Kennedy et al, 1988). Their electron microscopic results are similar to those reported here in that myofilamentous disruptions were noted in the majority of fibers examined during the first week of stretch.…”
Section: Discussionsupporting
confidence: 90%
“…Stretch-induced hypertrophy of avian wing muscle has also been implicated in the activation of satellite cells (Kennedy et al, 1988). Their electron microscopic results are similar to those reported here in that myofilamentous disruptions were noted in the majority of fibers examined during the first week of stretch.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, data from stretched ALD in immature chickens (Kennedy et al 1986(Kennedy et al , 1988Sweeney et al, 19891, appear consistent with data from overloaded rat muscle.…”
supporting
confidence: 83%
“…The relative increase of SM2 expression is consistent with the work of colleagues (1986,1988) who found an increase in the developmentally regulated increase in SM2 and down-regulation of SM1 in the immature chicken. However, it is important to note that unlike the report of Kennedy et al (1986Kennedy et al ( , 1988, the quail in this study were physically mature, so that the shift in isoform expression cannot be attributed to an increase in the rate of developmentally regulated events.…”
Section: Discussioncontrasting
confidence: 56%
“…Kennedy et al (1988) reported myofibril disruption in the stretched ALD muscles of chicken. Recently, we have reported evidence of fiber necrosis and regional injury in the stretch-enlarged ALD muscle (Winchester et al, 1991b).…”
Section: Bmentioning
confidence: 96%